Social anxiety and cigarette smoking in adolescents: the mediating role of emotional intelligence - Abdollahi, Abbas; Yaacob, Siti Nor; Abu Talib, Mansor; Ismail, Zanariah (Springer, 2015)
Smoking is one of the more common preventable threats to public health, and it remains a serious cause of death around the world. Remarkably, the mean age of the onset of cigarette smoking is decreasing. Therefore, it is necessary to increase our knowledge concerning the attitude among high school students towards cigarette smoking. The present study sought to examine the associations among social anxiety, emotional intelligence, and attitudes towards cigarette smoking, and to examine emotional intelligence as a mediator between social anxiety and attitude towards cigarette smoking. The participants comprised 950 high school students who completed the Liebowitz Social Anxiety Scale, Assessing Emotions Scale, and Attitudes Towards Cigarette Smoking Scale. Structural equation modelling analyses indicated that high levels of emotional intelligence are negatively associated with positive attitude towards cigarette smoking and social anxiety is associated with a positive attitude towards cigarette smoking in high school students. Emotional intelligence partially mediated the relationship between social anxiety and attitude towards cigarette smoking. These relationships varied as a function of gender.